ANALISIS USAHATANI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DI KOTA PEKANBARU - Rachmawaty Sri Cintami; Ermi Tety; Yusmini Yusmini (Indonesian Journal of Agricultural Economics, 2016)
The purpose of this research was to analyzed profit, break event point and efficiency of oyster mushroom farming at Pekanbaru City. Population of this research are 10 (ten) oyster farmer. This research used survey method, to analyze the profit, break event point and efficiency of oyster mushroom farmer used production cost formula, equipment depreciation formulafarm receipts formula and farming profits formula. Farming group determination of the amount of cultivated baglog, that are first group is 1.000-2000 baglog, second group is >2.000-3.000 baglog, and the third Group is ≥4.000-5.000 baglog. The result of this research showed average of farming income for one planting period, for first scale group is Rp.9.593.614,67 with BEP 318,20 Kg, for second group is Rp.17.384.527,78 with BEP 422,53 kg, and for third group are Rp.29.125.910,00 with BEP 510,01 kg. Farming efficiency result for first group are 1,93 it means output Rp.1,00 get profit Rp.0,93 and worthy to be developed, for second group are 2,21 it means output Rp.1,00 get profit Rp.1,21, and for third group are 2,50 it means output Rp.1,00 get profit Rp.1,50 and this oyster mushroom business worthy to be continued.